2010
DOI: 10.1111/j.1439-0310.2010.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence that Sexual Displays are Costly for Nest Survival

Abstract: Nest predation is one of the most significant limitations for successful breeding of tropical passerines. Thus, parental strategies may include choosing appropriate nest sites and behaving in ways that minimize predation. Habitat characteristics that may influence nest success include degree of nest concealment, proximity to habitat edge, plant architecture as well as several others cited in the literature. However, few studies have examined display behavior as a factor that could also influence nest survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…To test this hypothesis, we used artificial nests baited with quail eggs introduced into displaying Blue-black Grassquit male territories and compared their rate of predation with similar nests placed in comparable vegetation and heights, but which lacked the presence of a displaying male. We found that predation rate was significantly higher when nests were associated with displaying males (Dias et al 2010). The results of this experiment bring into sharp focus the tradeoffs associated not only with the display itself but also relative to the female dilemma when choosing a mate.…”
Section: Vulnerability To Nest Predatorsmentioning
confidence: 79%
See 1 more Smart Citation
“…To test this hypothesis, we used artificial nests baited with quail eggs introduced into displaying Blue-black Grassquit male territories and compared their rate of predation with similar nests placed in comparable vegetation and heights, but which lacked the presence of a displaying male. We found that predation rate was significantly higher when nests were associated with displaying males (Dias et al 2010). The results of this experiment bring into sharp focus the tradeoffs associated not only with the display itself but also relative to the female dilemma when choosing a mate.…”
Section: Vulnerability To Nest Predatorsmentioning
confidence: 79%
“…One recent experimental field study produced suggestive evidence that the leaping displays of male Blue-black Grassquits are costly in terms of nest survival (Dias et al 2010). This study was developed due to suggestions in the literature that several parental and offspring behaviors may attract predators to the nest, including begging by chicks and feeding trips by parents (Skutch 1949;Haskell 1994;Leech and Leonard 1997;Martin et al 2000).…”
Section: Vulnerability To Nest Predatorsmentioning
confidence: 98%
“…Our final scenario predicted that females would select more conspicuous male stimuli only in situations of low risk, and under high predation risk, they would choose male stimuli at random or even prefer more muted stimuli. This latter outcome assumed that association with vigorously displaying males might impose a great survival cost on females or their potential offspring (Dias et al, ; Marzal et al, ). Our results confirmed the first predicted scenario, given that females were non‐responsive to male song stimuli, whether at low or high rates, across all experimental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Males maintain their sexual displays even after establishing a socially monogamous breeding pair (Macedo et al, ), probably to attract neighboring females to obtain extrapair copulations (Carvalho, Macedo, & Graves, ; Manica et al, ). Males perform these conspicuous displays despite having an active nest in their territories, and this has been shown to increase predation risk for nests (Dias, Castilho, & Macedo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation